2016
DOI: 10.1161/atvbaha.116.307526
|View full text |Cite
|
Sign up to set email alerts
|

Bone Morphogenetic Protein Signaling Is Required for Aortic Valve Calcification

Abstract: Objective Calcific Aortic Valve Disease (CAVD) is the most prevalent type of heart valve disease, affecting ~2% of the US population. CAVD is characterized by the presence of calcific nodules resulting in aortic valve (AoV) stenosis; however, the underlying mechanisms driving disease remain unknown. Studies of human diseased AoV provide initial evidence that BMP signaling, essential for normal bone formation, is activated during CAVD. Mice deficient in Klotho, an FGF23 transmembrane co-receptor, exhibit premat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
56
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 48 publications
8
56
0
1
Order By: Relevance
“…The Klotho −/− mouse model, which exhibits premature aging associated with hyperphosphatemia and low vitamin D, has been used to study age-related diseases, including CKD and vascular calcification. Klotho −/− mice exhibit aortic valve calcification at the hinge region of the fibrosa side [16], a pathological change similar to human CAVD. Reduced expression of this protein has been observed in patients with CKD, and this may be one of the factors underlying the aortic valve calcification in CKD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Klotho −/− mouse model, which exhibits premature aging associated with hyperphosphatemia and low vitamin D, has been used to study age-related diseases, including CKD and vascular calcification. Klotho −/− mice exhibit aortic valve calcification at the hinge region of the fibrosa side [16], a pathological change similar to human CAVD. Reduced expression of this protein has been observed in patients with CKD, and this may be one of the factors underlying the aortic valve calcification in CKD.…”
Section: Discussionmentioning
confidence: 99%
“…Klotho levels in the kidney and blood were lower in patients with CKD [15]. Klotho-deficient mice suffer from a wide variety of age-related disorders as well as tissue calcification, including aortic valve calcification [16, 17]. However, it remains unknown whether Klotho suppresses high Pi-induced osteogenic responses in human AVICs.…”
Section: Introductionmentioning
confidence: 99%
“…It has been well established that BMP2, BMP4 and pSMAD1/5/8 are associated with aortic valve calcification [33], but a recent study by Gomez-Stallons et al demonstrated that BMP signaling is also required for aortic valve calcification in the Klotho −/− mouse model, which exhibits CAVD and premature aging associated with hyperphosphatemia. It was found that BMP signaling precedes and localizes with calcification in the aortic valve, and inhibition of BMP in VICs in vitro and in vivo prevents calcification [48]. Additional recent studies have further support the role of cadherin signaling in CAVD.…”
Section: Molecular Pathways For Aortic Valve Calcificationmentioning
confidence: 97%
“…However, a recent paper has shown that deletion of Bmpr1a with a PostnCre (Lindsley et al ., 2007) mesenchymal lineage driver line do not cause aortic or mitral valve defects at PD1 (Gomez-Stallons et al ., 2016). In the present study, we demonstrate that Bmp2 cKO Endo mice consistently exhibit membranous VSDs (Fig.…”
Section: Discussionmentioning
confidence: 99%